Surface Plasmon Resonance in Periodic Hexagonal Lattice Arrays of Silver Nanodisks. (3rd October 2013) - Hu, Jinlian; Wang, Cong; Yang, Shikuan; Zhou, Fei; Li, Zhigang; Kan, Caixia
Abstract : The surface plasmon resonance (SPR) of periodic hexagonal lattice arrays of silver nano-disks positioned on glass slides is studied using finite-difference time domain (FDTD) simulations. We investigate numerically the influence of diameter of nano-disks and the gap between nano-disks on SPR transmission spectra and electric field enhancement. We find a strong dependence of resonance wavelength on diameter of the nanodisks. With increasing the gap, electric field enhancement factor could significantly increase and reach a maximum value, which indicates that a special long-range interaction plays an important role. This study is useful for optical modulation applied in near or far field optics, sensing and data storage, and solar cell.